(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Nandrolone is an anabolic steroid drug that increases production and urinary excretion of erythropoietin. The drug is indicated with calcium nitrate, magnesium sulfate and potassium permanganate as concomitant uses. Therefore, there is a chance of interactions during concomitant use. Hence, we evaluated the interactions monitored by UV, conductometric titration and Ardon’s spectrophotometric methods of nandrolone with calcium nitrate, magnesium sulfate and potassium permanganate at the ratio of 1: 1 at different pHs. It was found that nandrolone did not form any stable complexes at the ratio of 1:1 with the above mentioned salts. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14554 Dhaka Univ. J. Pharm. Sci. 11(2): 93-99, 2012 (December)